THE VALIDITY OF A METHOD IN ARCHAEOLOGY: ON THE PROPOSAL FOR CULTURAL PERIOD OF ANDINA AREA BY JOHN H. ROWE - Del Águila Chávez, Carlos (2010)
The original idea of the this paper has been waiting from the year 2006 in order that it could be published by the MNAAHP, which I directed these years, together with another group of articles dedicated to evaluating Rowe’s theoretical - methodological work. This publishing project, that we call it in that opportunity “ Honoring to John Rowe “, could not be realized in spite of the efforts of the executives of the Pueblo Libre Museum. Nevertheless, I must recognize the valuable and intelligent detachment of his current director Christian Mesía in order that, for the sanmarquinas editions, we could publish some of these materials. The best recognition for Craig Morris is to publish these articules that approach the cultural sequence of Chincha and reconsiders the strengths of a method that, to the own one to say of Craig: It refuses to die.